2020
DOI: 10.1016/j.gene.2019.144058
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia and nutrient deprivation alter viability of human adipose-derived mesenchymal stem cells

Abstract: Purpose-Adipose-derived mesenchymal stem cells (MSCs) are attractive biological agents in regenerative medicine. To optimize cell therapies, it is necessary to determine the most effective delivery method for MSCs. Therefore, we evaluated the biological properties of MSCs after exposure to various temperatures to define optimal storage conditions prior to therapeutic delivery of MSCs. Design-Prospective observational studyMethods and materials-Adherent and non-adherent MSCs were incubated at multiple temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Therefore, the remarkable increase in FGF-2 secretion was probably connected with processes that occurred during storage. It is known that the prolonged storage of cells and tissues below physiological temperatures results in the moderation of metabolic activity and cell cycle deceleration or the initiation of apoptotic processes [47]. In this study, the significant upregulation of P21 was detected after 2 and 6 days of storage, indicating the possible temperature-induced cell cycle arrest.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, the remarkable increase in FGF-2 secretion was probably connected with processes that occurred during storage. It is known that the prolonged storage of cells and tissues below physiological temperatures results in the moderation of metabolic activity and cell cycle deceleration or the initiation of apoptotic processes [47]. In this study, the significant upregulation of P21 was detected after 2 and 6 days of storage, indicating the possible temperature-induced cell cycle arrest.…”
Section: Discussionmentioning
confidence: 48%
“…MSCs are fundamentally responsive to subtle changes in their environment. MSCs respond to changes in atmospheric gases ( Lin et al, 2014 ; Gorgun et al, 2021 ; Roemeling-Van Rhijn et al, 2013 ; Ejtehadifar et al, 2015 ; Kang et al, 2019 ; von Bahr et al, 2019 ), temperature ( Stolzing et al, 2006 ; Kubrova et al, 2020 ; Shimoni et al, 2020 ), hydrostatic pressure ( Steward et al, 2012 ; Becquart et al, 2016 ; Pattappa et al, 2019 ) and aggregation ( Robb et al, 2019 ; Yuan et al, 2019 ; Burand et al, 2020 ; Xie et al, 2021 ). It is surprising then, that the steps and duration between dose preparation and delivery of MSC therapies are ill-defined and under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized three possible causes of poor cell-delivery efficiency during intravenous infusion: (1) acute cell death due to nutrient deprivation and hypoxic stress in the suspension solution or biomechanical stress during infusion; (2) cell adhesion to the walls of the apparatus, such as the infusion bag, syringe, or infusion tube; and (3) cell aggregation during storage and infusion. Temperature, solution type, and cell density of the cell preparation, as well as storage, can affect the metabolic activity of MSC, thus altering their viability and function [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. It has been reported that the viability of hADSC in NS is better maintained at lower temperatures (4 °C) than at room temperature (37 °C) [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the viability of hADSC in NS is better maintained at lower temperatures (4 °C) than at room temperature (37 °C) [ 42 , 43 ]. On the other hand, Kubrova et al compared the viabilities of hADSC suspended in lactate Ringer’s solution and stored at physiological temperature (37 °C), room temperature (23 °C), or low temperature (4 °C) for 4 h, and reported that room temperature was optimal [ 44 ]. Because the current study focused on cell delivery in infused ADSC immediately after preparation, we considered the effect of temperature-related acute cell death to be minimal due to their short storage time, and we therefore prepared the cADSC at room temperature in this study.…”
Section: Discussionmentioning
confidence: 99%